Longer interval between first colonoscopy with negative findings for colorectal cancer and repeat colonoscopy - Liang, Qun-Feng; Mukama, Trasias; Sundquist, Kristina; Sundquist, Jan; Brenner, Hermann; Kharazmi, Elham; Fallah, Mahdi (JAMA oncology, 2024)
For individuals without a family history of colorectal cancer (CRC), colonoscopy screening every 10 years is recommended to reduce CRC incidence and mortality. However, debate exists about whether and for how long this 10-year interval could be safely expanded.To assess how many years after a first colonoscopy with findings negative for CRC a second colonoscopy can be performed.This cohort study leveraged Swedish nationwide register-based data to examine CRC diagnoses and CRC-specific mortality among individuals without a family history of CRC. The exposed group included individuals who had a first colonoscopy with findings negative for CRC at age 45 to 69 years between 1990 and 2016. The control group included individuals matched by sex, birth year, and baseline age (ie, the age of their matched exposed individual when the exposed individual’s first colonoscopy with findings negative for CRC was performed). Individuals in the control group either did not have a colonoscopy during the follow-up or underwent colonoscopy that resulted in a CRC diagnosis. Up to 18 controls were matched with each exposed individual. Individuals were followed up from 1990 to 2018, and data were analyzed from November 2022 to November 2023.A first colonoscopy with findings negative for CRC, defined as a first colonoscopy without a diagnosis of colorectal polyp, adenoma, carcinoma in situ, or CRC before or within 6 months after screening.The primary outcomes were CRC diagnosis and CRC-specific death. The 10-year standardized incidence ratio and standardized mortality ratio were calculated to compare risks of CRC and CRC-specific death in the exposed and control groups based on different follow-up screening intervals.The sample included 110074 individuals (65 147 females [59.2%]) in the exposed group and 1981332 (1 172 646 females [59.2%]) in the control group. The median (IQR) age for individuals in both groups was 59 (52-64) years. During up to 29 years of follow-up of individuals with a first colonoscopy with findings negative for CRC, 484 incident CRCs and 112 CRC-specific deaths occurred. After a first colonoscopy with findings negative for CRC, the risks of CRC and CRC-specific death in the exposed group were significantly lower than those in their matched controls for 15 years. At 15 years after a first colonoscopy with findings negative for CRC, the 10-year standardized incidence ratio was 0.72 (95% CI, 0.54-0.94) and the 10-year standardized mortality ratio was 0.55 (95% CI, 0.29-0.94). In other words, the 10-year cumulative risk of CRC in year 15 in the exposed group was 72% that of the 10-year cumulative risk of CRC in the control group. Extending the colonoscopy screening interval from 10 to 15 years in individuals with a first colonoscopy with findings negative for CRC could miss the early detection of only 2 CRC cases and the prevention of 1 CRC-specific death per 1000 individuals, while potentially avoiding 1000 colonoscopies.This cohort study found that for the population without a family history of CRC, the 10-year interval between colonoscopy screenings for individuals with a first colonoscopy with findings negative for CRC could potentially be extended to 15 years. A longer interval between colonoscopy screenings could be beneficial in avoiding unnecessary invasive examinations.
Online veröffentlicht 2. Mai 2024
Gesehen am 06.05.2024